Digital-Based Tourism Business Development Plan in Baros Tourism Village - Elmia, Arini Shofi; Putra, Rifki Rahmanda; Wirakusuma, Reiza Miftah (Journal of Business on Hospitality and Tourism, 2023)
Baros Tourism Village has a variety of tourism potentials managed by the community. Pesona Sampalan Indah is a swimming pool attraction managed by Badan Usaha Milik Desa (BUMDES) in the Baros Tourism Village, Bandung Regency. The purpose of this research is to formulate a tourism business plan for Pesona Sampalan Indah swimming pool attraction by implementing the concept of digital tourism through the Business Model Canvas (BMC) approach. New business development is analyzed by using SWOT analysis. SWOT analysis was conducted to determine the condition of internal factors and external factors. This research results in nine strategy formulations that can be implemented by the community and the surrounding environment by utilizing social media as a means of interaction with the operator and visitors themselves. This strategy was implemented to develop a business model for BUMDES in the Baros Tourism Village to be more competitive in generating income and welfare for the people involved.